Tanggung Jawab Penyedia Barang dan Jasa Melalui E-Marketplace Ditinjau dari Peraturan Perundang-Undangan Indonesia - Siregar, Yoko Firdaus Zamzam; Maharany, Utary; Lubis, Anggreni Atmei (Universitas Medan Area, 2024)
This research was conducted to know and understand the legal arrangements regarding the procurement of goods/services through e-marketplace, know and understand the process of goods/services procurement agreement through e-marketplace, and know and understand the legal responsibility of the engagement in the goods/services procurement agreement at the Medan City Personnel and Human Resources Development Agency. This research is a descriptive-analytical normative legal research. The data in this research is obtained based on literature studies and field surveys which are then analyzed with a qualitative approach. The results of this study indicate that the application of the electronic system does not change the structure of the project mechanism by Presidential Regulation No. 16 of 2018 concerning PBJ, but there are adjustments where the activities used to utilize the database system to be more efficient and productive while still being subject to the same supervision as the classic PBJ function. Implementation of purchasing goods/services Legal responsibility when participating with suppliers in the purchase and sale of goods/services contract at BKDPSDM Medan City must fulfill the requirements specified by law and be responsible for the execution and quality of the contract.